A revisit of the semi-geostrophic eddy east of the Sri Lanka dome with anisotropy insight - Le, Zhou; Subrahmanyam, M. V.; Raju, Pemmani Venkata Subba; Pathirana, Gayan; Wang, Dongxiao; Song, Wei (Frontiers in Marine Science, 2025)
As the Southwest Monsoon Current (SMC) turns northeastward to enter into the Bay of Bengal (BOB), a cyclonic dome develops east off Sri Lanka. Previous research has shown that an anticyclonic semi-geostrophic (SG) eddy can be generated on the further east side of SMC associated with kinetic energy transfer by barotropic instability (BTI). This study revisits the SG eddy using satellite altimetry data, reanalysis datasets and in-situ observations of Research Moored Array for African-Asian-Australian Monsoon Analysis and Prediction (RAMA). The results show that a cyclonic eddy-like (CE-like) negative Sea Level Anomaly (SLA), generated in the eastern BOB due to regional anomalous wind stress curl, also contributes to the formation of the SG eddy. During the formation, mean flows on the northern edge of the SG eddy are strengthened, and southeastward currents on the eastern edge are structured with the influence of CE-like SLA. Further instability analyses indicate that the anisotropic component of BTI is significantly larger than the isotropic one, attributed to the weak nonlinear planetary geostrophic convergence of the SG eddy and the CE-like SLA-induced strong horizontal shear in mean flow field. Additionally, this study points out that wind stress curl anomalies over the eastern BOB and subsequent formation of negative SLA are likely influenced by the Indian Ocean Dipole. These findings suggest that the coupling between SMC instability and regional wind stress curl may play a pivotal role in the generation of SG eddy on interannual timescale, with important implications for regional ocean dynamics.